Synchronized On/Off Switching of Four Binding Sites for Water in a Molecular Solomon Link. (7th May 2019) - Caprice, Kenji; Pupier, Marion; Bauzá, Antonio; Frontera, Antonio; Cougnon, Fabien B. L.
Abstract: A molecular Solomon link adopts different conformations in acetonitrile (1 ) and in water (2 ). Contrary to expectations, the main driving force of the transformation is not the change in medium polarity, but the cooperative binding of about four molecules of water, forming a tiny droplet in the central cavity of 2 . Mechanistic studies reveal that the four binding sites can simultaneously switch between an inactive state (unable to bind water) and an active state (able to bind water) during the transformation. Spatial and temporal coordination of switching events is commonly observed in biological systems but has been rarely achieved in artificial systems. Here, the concerted activation of the four switchable sites is controlled by the topology of the whole molecule. Abstract : Ganz oder gar nicht : Ein molekularer Salomonischer Knoten zeichnet sich durch vier voneinander abhängige Bindungsstellen aus, die in abgestimmter Weise zwischen einem inaktiven und einem aktiven Zustand schalten können. Im aktiven Zustand bindet jede Stelle ein Wassermolekül. Die Bindung von insgesamt vier Wassermolekülen an diesen ungewöhnlichen Rezeptor ist hoch kooperativ.